Medical disputes and patient satisfaction in China: How does hospital management matter?. (9th December 2021) - Wang, Mengxiao; Liu, Gordon Guo‐En; Bloom, Nicholas; Zhao, Hanqing; Butt, Thomas; Gao, Tianhao; Xu, Jiaqi; Jin, Xia
Abstract: Objective: Satisfaction with healthcare may be captured by surveys of patients and staff, or in extreme cases, the number and severity of medical disputes. This study tries to investigate the relationship between satisfaction and hospital management as well as the role of good management in preventing medical disputes ex ante. Method: We investigate this relationship using information on management practices collected from 510 hospitals in mainland China using the World Management Survey questionnaire and combined with medical malpractice litigation data and patient/staff satisfaction surveys. Multiple regression models were used to analyse the relationship between hospital management scores and medical litigation outcomes as well as patient and staff satisfaction during 2014–2016. Results: An increase of one standard deviation in the management score was related to 13.1% ( p < 0.10) lower incidence of medical disputes, 12.4% ( p < 0.05) fewer medical litigations, and 51.3% ( p < 0.10) less compensation. Better management quality of hospitals was associated with higher inpatient satisfaction ( p < 0.05) and staff well‐being ( p < 0.01). Conclusion: Improving hospital management could reduce hospital costs generated by lawsuits, reduce potential harm to patients, and improve patient and staff satisfaction, thus leading to a better patient‐physician relationship. Highlights: Management practices vary between Chinese hospitals Higher management scores were associated with less medical disputes Higher scores were also associated with higher patient and staff satisfaction Improving hospital management could reduce hospital costs and improve satisfaction